PENGARUH INTERNALISASI NILAI UKHUWAH ISLAMIAH DALAM PEMBENTUKAN KARAKTER RELIGIUS SANTRI DI PONDOK PESANTREN MODERN BANI TAMIM KABUPATEN TANGERANG - Maftuhah, Apap; Fikri Al-Fahm, Faiz; Setyawati, Ariesta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The internalization of Islamic values plays an important role in developing students' religious character in Islamic boarding schools. This study aimed to examine the effect of the internalization of ukhuwah Islamiah values on the religious character of students at Pondok Pesantren Modern Bani Tamim, Tangerang Regency. A quantitative approach with a correlational design was employed. The sample was selected using stratified random sampling, while data were collected through questionnaires, observation, and documentation. Data were analyzed using descriptive statistics, instrument validity and reliability tests, classical assumption tests, including the Ramsey RESET Test for model linearity, and simple linear regression with IBM SPSS Statistics version 25. The findings indicate that the internalization of ukhuwah Islamiah values is categorized as good, while the students' religious character is categorized as high. The regression analysis revealed a positive and significant effect of the internalization of ukhuwah Islamiah values on students' religious character (t = 13.673; p < 0.05). The coefficient of determination (R²) was 53.1%, indicating that the internalization of ukhuwah Islamiah values contributed substantially to the development of students' religious character, while the remaining 46.9% was influenced by other factors. These findings highlight the importance of strengthening Islamic brotherhood values as an educational strategy to foster students' religious character in Islamic boarding schools.